CGIAR Research Program on Agriculture for Nutrition and Health - Plan of Work and Budget 2020 - CGIAR Research Program on Agriculture for Nutrition and Health (CGIAR Research Program on Agriculture for Nutrition and Health, 2020)
The goal of A4NH is to strengthen the capacity of CGIAR to contribute globally to CGIAR’s second System Level Outcome (SLO2) on improved food and nutrition security for health and the 2030 Agenda for Sustainable Development.